Effects of moderate- and high-intensity aerobic training program in ambulatory subjects with incomplete spinal cord injury–a randomized controlled trial. Issue 10 (October 2018) - Wouda, Matthijs; Lundgaard, Eivind; Becker, Frank; Strøm, Vegard
Abstract Study Design Randomized controlled trial. Objectives To investigate if high-intensity interval training (HIIT) exhibits a higher increase in physical capacity and activity levels compared to moderate-intensity training (MIT) and treatment as usual. Setting Sunnaas Rehabilitation Hospital. Methods Thirty ambulatory participants with incomplete spinal cord injury (SCI) were recruited at discharge from inpatient rehabilitation. Two intervention groups performed a 12-week individual training program at home by walking or running, depending on their physical ability. The MIT group was instructed to exercise three times a week at 70% of maximal heart rate (HRmax), while the HIIT group was instructed to exercise twice a week at 85–95% of HRmax. The control group received treatment as usual. Pre- and post-tests consisted of maximal exercise testing on a treadmill (peak oxygen uptake (peak VO2 )), a 6-min walking test (6MWT), and 7 days of continuously activity monitoring (total daily energy expenditure (TDEE) and daily number of steps). Results The HIIT, MIT, and control groups showed an increase in peak VO2 from pre- to post-test. However, no between-group difference in physical capacity (peak VO2 and 6MWT) and physical activity levels (TDEE and daily number of steps) were found between these groups. Conclusions Performing HIIT did not exhibit a greater increase in physical capacity and activity levels than performing MIT or "treatment as usual" in ambulatory participants with SCI. Further studies are needed to elucidate both short- and long-term effects of HIIT and MIT in this SCI subpopulation.